Коли Тмутаракань стала володінням Русі? - Бубенок, О.Б. (Княжа доба: історія і культура, 2016)
Автор не підтримує ідеї тих дослідників, які вважають, що в Тмутаракані руси
могли закріпитися в IX – першій половині
Х ст. Найслушнішою є думка, що Таманський півострів князь Володимир захопив
до кінця 988 р. Але немає жодного писемного підтвердження того, що це сталося під час
Корсунської кампанії. Тому найбільший інтерес викликає повідомлення “Повісті минулих літ” про похід проти болгарів 985 р.,
а також свідчення Якова Мниха про захоплення земель “срібних болгарів” та хозарів. Порівняльний аналіз інформації цих двох
текстів дозволив дійти висновку, що йдеться про одні події – про похід князя Володимира до Східного Приазов’я та Тамані, а не до
Волзької Булгарії. Є підстави вважати, що термін “срібні болгари” являв собою лише
зовнішню назву з боку східних слов’ян і означав “багаті болгари”. Тому ніщо не заважає
вважати, що Яків Мних назвав “срібними” саме празовських болгарів. Author of this article does not support the
ideas of researchers who think, that the Rus’ian
people could take Tmutarakan’ in IX – the first
half of Х century AD. Most just is an idea, that
Taman’ peninsula was taken by prince Volodymyr
before the end of 988 AD. However we have
not even a single writing confirmation of that it
happened during Korsun’ campaign. Therefore
the data of “Story of Temporal Years” about the
military raid of prince Volodymyr against the
Bulgarians in 985 AD and also the information
of Jacob Mnikh about the prince Volodymyr’s
invasion of the lands of “the Silver Bulgarians”
and the Khazars are most interest. Comparative
analysis of information of these two texts allowed to reach to the conclusion, that in its we can see
one event – the military raid of Volodymyr to the Eastern coast of Azov Sea and Taman’ peninsula,
but not to the Volga Bulgaria. We have arguments to consider, that a term “the Silver Bulgarians”
was only the external name from the East Slavs and meant “the Rich Bulgarians”. Therefore we
can believe, that Jacob Mnikh named “Silver” exactly the Azov Sea Bulgarians.